2003
DOI: 10.1177/009145090303000406
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how Families Cope with Alcohol Problems in the UK West Midlands Sikh Community

Abstract: Twenty-four British Sikh wives of men with identified alcohol problems, plus ten of their husbands and seven of their daughters, were interviewed using a semistructured procedure that focused upon the ways in which wives and daughters had attempted to cope with their husbands'/fathers’ excessive drinking. In addition each completed the Coping Questionnaire (CQ) which has the same focus (husbands were instructed to indicate ways in which their wives had coped). Interview data were analyzed according to the grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Several studies have noted that Punjabi Sikh men, in particular, are at higher risk of alcohol abuse than any other South Asian group (i.e. Hindu and Muslim men) (Cochrane and Bal 1990;Ahuja, Orford, and Copello 2003;Agic 2004;Morjaria-Keval 2006). Singh and Tatla indicate alcohol misuse has 'always been very high among Sikhs, with the per capita rate among Sikhs of Punjab among the highest in the world ' (2006, 177).…”
Section: Substance Misuse In Punjabi Sikh Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have noted that Punjabi Sikh men, in particular, are at higher risk of alcohol abuse than any other South Asian group (i.e. Hindu and Muslim men) (Cochrane and Bal 1990;Ahuja, Orford, and Copello 2003;Agic 2004;Morjaria-Keval 2006). Singh and Tatla indicate alcohol misuse has 'always been very high among Sikhs, with the per capita rate among Sikhs of Punjab among the highest in the world ' (2006, 177).…”
Section: Substance Misuse In Punjabi Sikh Communitiesmentioning
confidence: 99%
“…He advises that such a pro-alcohol attitude 'plays an influential role in the socialization of Punjabi males; that is, they internalize the cultural belief that alcohol consumption is indeed an aspect of their masculinity' (Sandhu 2009, 26). Purser et al (2001, cited in Ahuja, Orford, andCopello 2003) found second-generation Sikh men were more often drinkers -and were more likely to drink in a risky manner -than their Hindu or Muslim counterparts. South Asians in the West may also view alcohol as a way to relax, reduce stress, deal with problems at home, reduce loneliness and may also consider it to be a means to become more sociable (Agic 2004).…”
Section: Substance Misuse In Punjabi Sikh Communitiesmentioning
confidence: 99%
“…These data were both quantitative and qualitative, and include material from the UK alone (Ahuja, Orford, & Copello, 2003) and in comparison with Mexico (Orford et al, 1998a(Orford et al, ,b, 1999(Orford et al, , 2001, and from Australian Aboriginal communities alone (Orford, Templeton, Copello, Velleman, & Bradbury, 2000) and in comparison with other data (Mathews & Velleman, 1997;Orford et al, 2005a).…”
Section: The Stress-strain-coping-support (Sscs) Modelmentioning
confidence: 99%
“…Previous research has demonstrated that family members across widely different societies and communities have similar experiences in dealing with a substance misusing relative. This previous research has investigated family members within comparatively economically advantaged urban and rural areas of the southwest of England (with all that this implies in terms of economic advantage and environmental cushioning; Orford et al 1998aOrford et al , b, 1999; among Sikh families in the West Midlands (Ahuja, Orford & Copello 2003); within Mexico City, in a largely economically deprived population (urban slum dwellers) with issues of poverty, overcrowded accommodation, and environmental pollution being high on people's agendas (Orford et al 1998a(Orford et al , b, 1999(Orford et al , 2001; and with both urban and rural indigenous Aboriginal inhabitants in the Northern Territory, Australia, where similar issues of economic deprivation exist, coupled with major cultural dislocation and institutionalized racism (Mathews & Velleman 1997;Orford et al 2000;Orford et al 2005b). …”
Section: Alcohol and Drug Problems As Family Crisesmentioning
confidence: 99%